Pengaruh Profitabilitas, Leverage, Komisaris Independen, dan Tipe Industri Terhadap Pengungkapan Sukarela - Nurmalitasari, Anneke; Widiyaningsih, Vitalis Ari (Journal of Economics Business Finance and Accounting, 2023)
This study aims to find out the results of the Voluntary Disclosure Analysis in terms of Profitability, Independent Commissioners, Leverage and Industry Type in consumer goods sector companies listed on the IDX in 2018-2022. Sampling technique from secondary data. Secondary data is data obtained by researchers from various existing sources. The number of companies that were sampled was 37 companies. The analytical method used is multiple linear regression analysis which is processed using the SPSS ver. 25 to be able to test the independent variables on the dependent variable. The results of research hypothesis testing show that the profitability variable has a negative and significant effect on voluntary disclosure, while independent commissioners and leverage have a positive and significant effect on voluntary disclosure. Meanwhile, in the dummy regression, industry type as proxied by profile has a positive effect on voluntary disclosure.